2021
DOI: 10.11646/zootaxa.4991.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Towards resolving the problematic status of the digenean genus Astiotrema Looss, 1900: An updated concept and revision of species composition for Astiotrema (sensu stricto)

Abstract: Species of Astiotrema Looss, 1900 (sensu lato) infect a wide range of fishes, amphibians and reptilians. They also possess a considerably wide spectrum of morphological features. Several species were recognized for variable, confusing, overlapping and unspecialized morphological characters rather than for unique distinguishing features, causing continuing dispute around the validity of several species. Following comprehensive review, a revised restricted concept of Astiotrema is proposed including a morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 613 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The genus Astiotrema, which belongs to the Plagiorchiidae, represent trematodes infecting a wide range of fishes, amphibians, and reptilians. Many reports have indicated that Astiotrema (sensu stricto) is widely spread throughout Asia, Europe, and Africa, particularly in northeastern Africa (Egypt, Sudan), eastern Asia (China, southern Korea), southern Asia (India, Pakistan), southeastern Asia (Myanmar), northern Asia (Russia), and central Europe (Poland) (Karar et al 2021). However, several authors were unclear as to the diagnostic features of Astiotrema used, which are considered to be highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Astiotrema, which belongs to the Plagiorchiidae, represent trematodes infecting a wide range of fishes, amphibians, and reptilians. Many reports have indicated that Astiotrema (sensu stricto) is widely spread throughout Asia, Europe, and Africa, particularly in northeastern Africa (Egypt, Sudan), eastern Asia (China, southern Korea), southern Asia (India, Pakistan), southeastern Asia (Myanmar), northern Asia (Russia), and central Europe (Poland) (Karar et al 2021). However, several authors were unclear as to the diagnostic features of Astiotrema used, which are considered to be highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…The 28S sequence of our cercaria (ON312624) matched those of species in the genus Astiotrema Looss, 1900 and of Tremiorchis ranarum Mehra & Negi, 1926 (MT218013) at over 96% of sites. Tremiorchis Mehra & Nega, 1926 is often regarded as a junior synonym of Astiotrema (see Karar et al ., 2021; Shinad et al ., 2021). The next-best 28S matches were much lower (~87%) and were with campulids, brachycladiids and acanthocolpids, none of which is a likely home for this cercaria.…”
Section: Resultsmentioning
confidence: 99%